Preparedness, Challenges and Coping Mechanisms of Teachers and School Heads in the Implementation of Face-to-face Classes in Zone 2, Schools Division of Zambales, Philippines - Anastacio, Karen V. (Future Science / FSH-PH Publications, 2025)
This study examines the preparedness, challenges, and coping mech-anisms of teachers and school heads in implementing face-to-face classes in Zone 2, Schools Division of Zambales. Using a descriptive-quantitative approach, the study surveyed 228 teachers and 13 school heads. Findings reveal that teachers and school heads are highly pre-pared, though challenges persist in workload management and re-source availability. Statistical analysis shows a significant difference in preparedness levels between teachers and school heads, but no significant difference in perceived challenges and coping mechanisms. Furthermore, no correlation was found between preparedness and challenges, as well as between challenges and coping mechanisms, suggesting that preparedness is independent of encountered chal-lenges. The study highlights the need for ongoing training and support for educators.